Analysis of Land Cover Change Trends at Rejoso Watershed, Pasuruan Regency, East Java Province - Nurrohma Amalia, Nadhea; Suhartanto , Ery; Andawayanti, Ussy (Fakultas Teknik, Universitas Brawijaya, 2024)
Human activities such as urbanization, population growth, agricultural expansion, deforestation, and industrialization significantly influence changes in land cover and the environment. The United Nations World Urbanization Prospects reports that by 2030, around 60% of the world’s population will live in cities, increasing from 54% in 2014 to 66% in 2050. This change in land cover can cause environmental disasters such as erosion and flooding, resulting in biodiversity loss, land degradation, and pollution. Therefore, monitoring land cover changes is a priority for researchers and policymakers. This research analyses land cover changes from 2012, 2017, and 2022, predicting 2027 and 2032. Landsat satellite image processing to create land cover maps for 2012, 2017, and 2022 uses a supervised classification method in GIS software and predicts land cover for 2027 and 2032. It was carried out with the help of TerrSet software with a CA-Markov model using spatial data on land cover maps for 2012, 2017, and 2022. The results of this process show that land cover of lakes, forests, plantations, and rice fields decreased in each period, while land cover of dry land, residential areas, bushes, and ponds experienced an increase. The result validation value in 2012 was 81.98%, in 2017, 76.83%, and in 2022, 79.57%, and validation in 2022 on Terrset of 0.7190.